Pulsed DC Sputtering of Highly c‐Axis AlN Film on Top of Si (111) Substrate. Issue 6 (14th April 2021) - Iqbal, Abid; Walker, Glenn; Hold, Leonie; Fernandes, Alanna; Iacopi, Alan; Mohd-Yasin, Faisal
Abstract : Herein, pulsed DC sputtering of the AlN film on top of the Si (111) substrate is reported on. First, major articles on the reactive sputtering of AlN film on top of Si (111) substrate that were published in the past 30 years are tabulated. Then, a sputtering recipe to produce a consistent and high‐crystal‐quality (as measured by the full width at half maximum [FWHM] of rocking curve) AlN film across varying substrate temperatures (250–450 °C) and sputtering powers (1200–2400 W) is proposed. In addition, the influence of both parameters to in‐plane stress is demonstrated, in agreement with similar trends that have been reported in the literature for AlN films on other substrates. The best sample is produced at a substrate temperature of 350 °C and sputtering power of 1800 W, resulting in FWHM of rocking curve of 1.84°, surface roughness of 1 nm, and in‐plane stress of +300 MPa. The recipe herein is beneficial for integration of AlN thin film in complementary metal–oxide–semiconductor and micro‐electromechanical system processes. Abstract : Herein, pulsed DC sputtering of AlN films on top of the Si (111) substrate is reported on. A sputtering recipe to produce a consistent and high‐crystal‐quality (as measured by full width at half maximum of the rocking curve) AlN film across varying substrate temperatures (from 250 °C to 450 °C) and sputtering powers (1200–2400 W) is proposed.